Exotic species are perceived more than native ones in a megadiverse country as brazil - MELO,ERIKA P.C. DE (2021)
Abstract Research on environmental perception is essential for the understanding of individuals’ relations and expectations towards natural environments. Here, we evaluated the perception of high school students on exotic and native species in Brazil. We interviewed 371 students from two high schools located in the state of Goiás, one with and one without a protected area within its premises. Students needed to identify native and exotic species and to indicate species origin. We used a t-test to evaluate differences between students’ scores regarding the correctness of species origin and also ANOVA to assess whether these scores varied among taxonomic groups. Students identified exotic species better than native ones. Students better identified exotic mammals, fishes, and birds than native ones. We found there were no significant relationships of students’ knowledge of species’ origins with socioecological factors. Students’ perceptions of exotic and native species were low and focused on charismatic large-bodied species. We suggest that students are encouraged to expand their knowledge of local biodiversity. Teachers, local schools, and policymakers are essential to achieve this aim. A more diverse methodology for teaching, including new technologies and citizen-science projects, can help establish a genuine interest of local biodiversity students.